Systematic Literature Review: The Role Of Transparency In Government Accounting - Almira Yumna Putri; Enggar Diah Puspa Arum; Wira Lestari (Cita konsultindo, 2026)
This research applies a Systematic Literature Review (SLR) to investigate the relationship between transparency and government accounting, including how these studies are distributed and categorized. Findings indicate that transparency in governmental accounting significantly enhances accountability, public confidence, and the overall quality of state financial administration. A large portion of the literature highlights that adopting accrual-based accounting standards, maintaining publicly accessible financial reporting, and utilizing information technology contribute positively to improving transparency outcomes. However, challenges such as insufficient human resource competence, lack of managerial commitment, and regulatory limitations still impede achieving optimal transparency in the public sector. Based on evidence from 14 national and international journal articles, transparency supports accountability and public trust, especially when combined with accrual-based accounting and information technology utilization, although limitations in expertise and institutional readiness remain barriers. This study offers a novel contribution by merging a systematic literature review approach with a focused analysis of transparency and government accounting within the 2016–2025 timeframe.